The Catholic Epistles and Apostolic Tradition - Niebuhr, Karl-Wilhelm; Wallace, Robert W. (Baylor Univ.Press, 2009)
The SNTS seminar on the Catholic Epistles (2001-2006) / Robert W. Wall and Karl-Wilhelm Niebuhr -- A unifying theology of the Catholic Epistles / Robert W. Wall -- James in the minds of the recipients / Karl-Wilhelm Niebuhr -- James and the Jesus tradition / Patrick J. Hartin -- The reception of the Jesus tradition in James / John S. Kloppenborg -- The historical context of the Letter of James in light of its traditio-historical relations with First Peter / Matthias Konradt -- Acts and James / Robert W. Wall -- The priority of James / Robert W. Wall -- James as the first Catholic Epistle / John Painter -- The Letter of James as a canon-conscious pseudepigraph / David R. Nienhuis -- Salvation and anthropology in First Peter / Reinhard Feldmeier -- First Peter as early Christian diaspora letter / Lutz Doering -- The Johannine Epistles as Catholic Epistles / John Painter -- The Epistle of Jude between Judaism and Hellenism / Jörg Frey -- Salvation in Jude 5 and the argument of 2 Peter 1:3-11 / Scott J. Hafemann -- A prolegomenon to a history of the "postapostolic era" (early Christianity 70-150 CE) / Ernst Baasland
Includes bibliographical references (p. ) and index
Keywords: Bible -- Catholic Epistles -- Criticism, interpretation, etc -- Congresses; Konferenzschrift; Bibel / Katholische Briefe